Disrupt of Intra-Limb APA Pattern in Parkinsonian Patients Performing Index-Finger Flexion - Bolzoni, Francesco; Esposti, Roberto; Marchese, Silvia M.; Pozzi, Nicoló G.; Ramirez-Pasos, Uri E.; Isaias, Ioannis U.; Cavallari, Paolo (Frontiers in Physiology, 2018)
Voluntary movements induce postural perturbations which are counteracted by anticipatory postural adjustments (APAs). These actions are known to build up long fixation chains toward available support points (inter-limb APAs), so as to grant whole body equilibrium. Moreover, recent studies highlighted that APAs also build-up short fixation chains, within the same limb where a distal segment is moved (intra-limb APAs), aimed at stabilizing the proximal segments. The neural structures generating intra-limb APAs still need investigations; the present study aims to compare focal movement kinematics and intra-limb APA latencies and pattern between healthy subjects and parkinsonian patients, assuming the latter as a model of basal ganglia dysfunction. Intra-limb APAs that stabilize the arm when the index-finger is briskly flexed were recorded in 13 parkinsonian patients and in 10 age-matched healthy subjects. Index-finger movement was smaller in parkinsonian patients vs. healthy subjects (p = 0.01) and more delayed with respect to the onset of the prime mover flexor digitorum superficialis (FDS, p < 0.0001). In agreement with the literature, in all healthy subjects the FDS activation was preceded by an inhibitory intra-limb APA in biceps brachii (BB) and anterior deltoid (AD), and almost simultaneous to an excitatory intra-limb APA in triceps brachii (TB). In parkinsonian patients, no significant differences were found for TB and AD intra-limb APA timings, however only four patients showed an inhibitory intra-limb APA in BB, while other four did not show any BB intra-limb APAs and five actually developed a BB excitation. The frequency of occurrence of normal sign, lacking, and inverted BB APAs was different in healthy vs. parkinsonian participants (p = 0.0016). The observed alterations in index-finger kinematics and intra-limb APA pattern in parkinsonian patients suggest that basal ganglia, in addition to shaping the focal movement, may also contribute to intra-limb APA control.